Pengaruh Komitmen Organisasi dan Perceived Organizational Support terhadap Turnover Intentions pada Karyawan Hotel Sahid Surabaya - SUGIARTO, CAHYO (Jurnal Ilmu Manajemen (JIM), 2018)
This study aims to examine the effect of independent variables Organizational Commitment and Perceived Organizational Support to Employee Turnover Intentions at Hotel Sahid. Data obtained from the results of questionnaires and interviews. Sample in this research counted 86 respondents taken with Probability sampling method. Data collection techniques used is a questionnaire technique distributed directly to respondents in this case is the employee Hotel Sahid Surabaya. Data analysis technique using multiple linear regression analysis. This study uses reliability test techniques, validity and classical assumptions. The results of this study indicate that Organizational Commitment and Perceived Organizational Support variables have a negative and significant effect on Employee Turnover Intentions at Hotel Sahid. Keywords: Organizational Commitment, Perceived Organizational Support , Turnover Intentions